A Characterization of the ALMA Phasing System at 345 GHz. (6th March 2023) - Crew, G. B.; Goddi, C.; Matthews, L. D.; Rottmann, H.; Saez, A.; Martí-Vidal, I.
Abstract: The development of the Atacama Large Millimeter/submillimeter Array (ALMA) phasing system (APS) has allowed ALMA to function as an extraordinarily sensitive station for very long baseline interferometry (VLBI) at frequencies of up to 230 GHz ( λ ≈ 1.3 mm). Efforts are now underway to extend the use of the APS to 345 GHz ( λ ≈ 0.87 mm). Here we report a characterization of APS performance at 345 GHz based on a series of tests carried out between 2015 and 2021, including a successful global VLBI test campaign conducted in 2018 October in collaboration with the Event Horizon Telescope.